Cyclic environmental changes during the Early Toarcian at the Mochras Farm Borehole (Wales): a variable response of the foraminiferal community. (12th July 2020) - Rodríguez‐Tovar, Francisco J.; Pardo‐Igúzquiza, Eulogio; Reolid, Matias
Abstract : Cyclostratigraphical analysis of the foraminiferal assemblages from the Early Toarcian at the Mochras Farm Borehole (Wales) was conducted in order to evaluate the incidence of cyclic palaeoenvironmental changes on the foraminiferal community. Different variables such as type of morphogroup, evolutionary strategy, habitat, particular taxa, diversity and abundance were studied using the Lomb–Scargle periodogram implemented in the computer program SLOMBS. A well‐developed cyclostratigraphical pattern is recognized, with the presence of several cycles (in metres) at 3.4–4/7.2–7.5/10.1–10.6/32.1–33.3/104.2–111.2/128.2/166.7, belonging to the high‐, middle‐, middle‐/low‐, and low‐frequency bands. The incidence and relevance of the cycles is found to be related to particular variables marking the global and local character of the involved processes. Cyclic changes in the organic matter input are found to be the most relevant palaeoenvironmental factor, oxygenation being secondary. A correspondence with specific Milankovitch cycles is, at present, difficult to determine.